Effectiveness of the BBIBP-CorV vaccine in preventing infection and death in health care workers in Peru 2021 - Silva-Valencia, Javier (2023)
Background: During 2021, Peru started the vaccination against SARS-CoV-2 using the BBIBP-CorV inactivated virus vaccine for health care workers (HCW). We aim to evaluate the effectiveness of the BBIBP-CorV vaccine to prevent SARS-CoV-2 infection and deaths among HCWs. Methods: Retrospective cohort study, from February 9 to June 30, 2021, using national registries of health care workers, laboratory tests for SARS-CoV-2 and deaths. We calculated the vaccine effectiveness for preventing laboratory-confirmed SARS-CoV-2 infection, COVID-19-mortality, and all-cause mortality among partially immunized and fully immunized HCWs. An extension of Cox proportional hazards regression was used to model the mortality results, and Poisson regression was used to model SARS-CoV-2 infection. Results: The study included 606,772 eligible HCWs, the mean age was 40 (IQR: 33.0, 51.0). In fully immunized HCW, the effectiveness for preventing all-cause mortality was 83.6 (95% CI: 80.2 to 86.4), 88.7 (95% CI: 85.1 to 91.4) for preventing COVID-19 mortality, and 40.3 (95% CI 38.9 to 41.6) for preventing SARS-CoV-2 infection. Conclusion: The BBIBP-CorV vaccine showed high levels of effectiveness for preventing all-cause and COVID-19 deaths among fully immunized HCW. These results were consistent within different subgroups and sensitivity analyses. However, the effectiveness for preventing infection was suboptimal in this particular setting.